Paradox Of Indonesia's Natural Rubber Export Competitiveness And The Improvement Of Farmers' Welfare - Guido Imanuel Pardede; Sikel Reinaldi Habeahan; Mawarni Sianturi; Jesika Lumbanraja; Oky Staycof Purba; Jongkers Tampubolon (Tropical Plantation Journal, 2026)
Natural rubber is a strategic commodity for Indonesia with a strong comparative advantage in the global market; however, this advantage is not reflected in the welfare of smallholder farmers. This study aims to analyze the paradox between Indonesia’s natural rubber export competitiveness and farmer welfare. A descriptive-comparative quantitative approach was employed using secondary data from 2010-2024 covering five major natural rubber exporting countries: Indonesia, Thailand, Vietnam, Côte d’Ivoire, and Malaysia. Export competitiveness was assessed using Revealed Comparative Advantage (RCA) and Revealed Symmetric Comparative Advantage (RSCA), while farmer welfare was evaluated through income, farm-gate rubber prices, and Farmer Exchange Rate (NTP) indicators. The results show that Indonesia consistently maintained a comparative advantage (RCA 1; RSCA 0), but competitiveness declined over time, with RCA decreasing from 32.47 in 2017 to 16.34 in 2024 and RSCA declining from 0.9321 in 2010 to 0.8847 in 2024. Meanwhile, farmer welfare remained vulnerable due to price volatility, low productivity, and weak bargaining power. These findings reveal a persistent paradox between strong export competitiveness and fragile farmer welfare. Therefore, integrated policies are needed to improve productivity, strengthen farmer institutions, stabilize prices, and promote downstream industrial development.